Prediction Of Stature From Length Of Distal Half Of Upper Limb (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: Establishment of identity is a real challenge when dead bodies are burnt, mutilated, or skeletonized. Stature is a very useful tool to establish the identity. Study of estimation of stature from the length of long bones are there in the literature, however the reliability of the formula is not consistent in many instances. The present study is an attempt to establish the relationship between stature and length of distal half of upper limb. Materials and methods: This cross sectional study was conducted on 100 subjects, 50 males and 50 females aged between 21 and 60 years in the department of Forensic Medicine in Govt. Medical College, Thrissur.  Results: In males the mean length of distal half of upper limb is 47.64 ± 1.41 cm. and correlation coefficient (r) is 0.8125. In females the mean length of distal half of upper limb is 43.94 ± 2.19 cm. and correlation coefficient (r) is 0.7458. Thus stature is strongly correlated with length of distal half of upper limb. Conclusion: There is significant difference between males and females with respect to both the parameters under study. The higher mean values obtained by males indicated that they have greater stature and length of distal half of upper limb measurements compared to females.
Keywords: Anthropometry, distal- half of upper-limb, stature, length.